Collaboratively seeking to improve contraceptive counselling at the time of an abortion: a case study of quality improvement efforts in Sweden. Issue 3 (9th July 2019) - Kilander, Helena; Brynhildsen, Jan; Alehagen, Siw; Fagerkrantz, Amanda; Thor, Johan
Abstract : Background: Many women find it difficult to choose and initiate a contraceptive method at the time of an abortion. There is a gap between regular clinical practice and existing evidence on motivational and person-centred counselling, as well as on use of long-acting reversible contraception (LARC). This study aims to describe and evaluate a Quality Improvement Collaborative (QIC) designed to enhance contraceptive services, with regard to changes in healthcare professionals' (HCPs') counselling in clinical practice, and in women's subsequent choice of, and access to, contraception. Methods: Three multiprofessional teams working in abortion services from three hospitals in Sweden, and two women contributing with user experience, participated in a QIC during the period March–November 2017. Using a case study design, we collected and analysed both quantitative and qualitative data. Results: Teams agreed on QIC goals, including that ≥50% of women would start LARC within 30 days post-abortion, and tested multiple evidence-based changes, aided by the two women's feedback. During the QIC, participating HCPs reported that they gained new knowledge and developed skills in contraceptive counselling at the time of an abortion. The teams welcomed the development of a performance feedback system regarding women's post-abortion contraception. While the majority of women counselled during the QIC chose LARC, only 20%–40% received it within 30 days post-abortion. Conclusion: The QIC, incorporating user feedback, helped HCPs to develop capability in providing contraceptive services at the time of an abortion. Timely access to LARC remains a challenge in the present setting.